STRATEGI GURU PENDIDIKAN AGAMA KATOLIK DALAM MENINGKATKAN KETERAMPILAN 4Cs SEKOLAH MENENGAH PERTAMA - Erikson Simbolon; Tampubolon, Fonelita Anatasya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The importance of this research is to analyze the strategies of Catholic Religious Education teachers in improving 4Cs skills (Critical thinking, Communication, Collaboration, and Creativity) in Junior High School. In the era of globalization and rapid technological development, 4Cs skills become very important to prepare students to face future challenges. The main purpose of this research is to find out the Catholic Religious Education Teacher's Learning Strategy and the Catholic Religious Education Teacher's Strategy in improving 4Cs Skills in Class VII Students of SMPS Santo Yoseph Medan. The method used in this research is descriptive qualitative with data collection techniques through observation, interviews and documentation. The research process begins with making observations in the field to obtain valid data regarding the Learning Strategy of Catholic Religious Education Teachers and improving 4Cs skills. Interviews were conducted with informants to explore and obtain in-depth information about the learning strategies of Catholic Religious Education Teachers and the improvement of 4Cs skills. Documentation was conducted by collecting various supporting documents related to the 4Cs skills improvement strategy, such as teaching modules and learning materials. Data processing techniques were carried out through reduction, display, and conclusion drawing. The place of this research is Santo Yoseph Junior High School Medan. The informants in this study were Catholic Religious Education subject teachers, co-teachers and students. The findings of this study are two-first, Catholic Religious Education teachers have set learning objectives, teaching materials and materials, learning methods, learning media, and evaluation. Second, Catholic Religious Education teachers apply the strategy of question and answer method, Think-Talk-Write method, group-based assignments, Practice, Project Based Learning.